ANALYSIS OF THE DETERMINANTS OF GOJEK DRIVERS INCOMEIN DENPASAR CITY - Putu Pande Ardiputra Nugraha; Ni Putu Martini Dewi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Community mobility requires adequate transportation services. The rapid advancement of technology has led to the emergence of online transportation, particularly application-based services that simplify access to mobility. One prominent example is online motorcycle taxis, such as Gojek, which not only offer transportation and delivery services but also create job opportunities with flexible working hours as a key attraction. The income earned by Gojek drivers is determined by various factors, including fares, working hours, the number of transactions completed, and performance-based incentives. This study investigates how these fares, working hours, number of transactions, and incentives affect the income of Gojek drivers in Denpasar City. This study aims to examine the influence of fares, working hours, number of transactions, and incentives on the income of Gojek drivers in Denpasar City, both simultaneously and individually, and to identify the most dominant factor affecting their income. The research was conducted in Denpasar City with a sample of 96 Gojek drivers selected through a convenience (incidental) sampling technique. Primary data were collected through observation, structured and unstructured interviews, as well as documentation. The research data were analyzed using multiple linear regression, supported by classical assumption tests, F-tests to assess the joint significance of the variables, t-tests to evaluate individual variable effects, and a dominance test to identify the most influential factor. The results show that fares, working hours, number of transactions, and incentives together significantly affect the income of Gojek drivers. In partial analysis, fares, number of transactions, and incentives show a positive and significant effect on income, whereas working hours have a positive but statistically insignificant influence. Among all the variables analyzed, the number of transactions is identified as the most dominant factor influencing the income of Gojek drivers in Denpasar City.